In-situ synthesis of Yttria-based precipitates and their effects on Fe12Cr6Al in laser powder bed fusion - Omer Cakmak; Hwasung Yeom; Jung-Wook Cho (Journal of Materials Research and Technology)
To advance the suitability of FeCrAl alloys for nuclear applications, radiation damage resistance, creep resistance, corrosion resistance, and mechanical properties enhancement are essential. A promising approach is the introduction of a high density of nitride and oxide nanoprecipitates within the alloy matrix. This study aimed to explore the impact of in-situ formed nitride and oxide precipitates on the properties of Fe12Cr6Al alloy by using a nitrogen-rich atmosphere and incorporating nano-sized Y2O3 (0.45 wt %) during laser powder bed fusion (LPBF). As a result of adding Y2O3 nanoparticles to the Fe12Cr6Al alloy, the grain size decreased from 70 μm to 40 μm, and the Al–O, Al–N, and Al–N–O precipitates were replaced by Y–O, Y–Al–O, and Y–N precipitates. Additionally, the nitrogen contents increased from 220 ppm to 470 ppm. The sample with Y2O3 exhibited higher mechanical properties, with yield strength, tensile strength, and hardness (HV) increasing by 80 MPa, 112 MPa, and 23 HV, respectively. This study deviates from previous research on Y2O3-containing FeCrAl alloys by investigating the impact of in-situ synthesized Y–N nitrides on Fe12Cr6Al. The objective is to elucidate the combined effects of these precipitates on the properties of Fe12Cr6Al alloy in comparison to literature-reported oxide dispersion-strengthened (ODS) FeCrAl alloys, which were fabricated in an argon (Ar) atmosphere.